2013
DOI: 10.1167/iovs.13-11630
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Anterior Segment Parameters After Laser Peripheral Iridotomy Assessed by Anterior Segment Optical Coherence Tomography

Abstract: The ACA tended to be narrowed at 18 months post-LPI despite resolution of pupillary block, which may be due to LV increment. Our results warrant continuous follow-up of narrow-angle patients after LPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 25 publications
4
44
3
1
Order By: Relevance
“…Using the AS-OCT in a group of 84 eyes of 52 angle closure suspects, it could be found that prophylactic LPI causes ACA to increase significantly and that narrower angles at baseline before LPI are associated with a more pronounced increase of ACA than wider angles [30]. Lee et al [31] could show that anterior chamber area and ACA increase after LPI in 32 eyes of 32 primary angle closure suspects but decreases again thereafter so that 18 months after LPI, a group of ACA indices are not statistically different from their pre-LPI values anymore.…”
Section: Discussionmentioning
confidence: 99%
“…Using the AS-OCT in a group of 84 eyes of 52 angle closure suspects, it could be found that prophylactic LPI causes ACA to increase significantly and that narrower angles at baseline before LPI are associated with a more pronounced increase of ACA than wider angles [30]. Lee et al [31] could show that anterior chamber area and ACA increase after LPI in 32 eyes of 32 primary angle closure suspects but decreases again thereafter so that 18 months after LPI, a group of ACA indices are not statistically different from their pre-LPI values anymore.…”
Section: Discussionmentioning
confidence: 99%
“…The image acquisition procedure and analysis method are described elsewhere in detail. 16,19,25,27 Analysis Previous studies reported increases in AOD as one of the most remarkable changes after LPI when assessed by AS OCT; 28-32 we therefore used proportional changes (%) in AOD 750 as outcome measures for LPI. Univariate and multivariate linear regression analysis were performed to evaluate the baseline AS parameters associated with proportional change in AOD 750 .…”
Section: As Oct Imagingmentioning
confidence: 99%
“…The aim of the current study was, therefore, to investigate baseline anterior segment (AS) features associated with the outcome of LPI. Furthermore, some angle closure eyes that show opening of the AC angle immediately post-LPI have been reported to show progressive narrowing of the angle or development of PAS; 11,19 thus, we also explored the baseline AS parameters associated with long-term outcome of LPI. Identifying baseline factors that are predictive of outcome of LPI would help determine whether LPI is mandatory in individual angle closure eyes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several imaging techniques have been used for anterior chamber depth (ACD) assessment: Scheimflug camera [1,2], scanning-slit topography [3,4], ultrasonic immersion instruments [5,6] and optical coherence tomography [7,8].…”
Section: Introductionmentioning
confidence: 99%